Patient satisfaction with healthcare services: Bangladesh perspective - Abdul Kader Mohiuddin (Intelektual Pustaka Media Utama, 2020)
Patient satisfaction is a useful measure for providing a quality benchmark for healthcare services. Concern about the quality of healthcare services in Bangladesh has led to a loss of confidence in healthcare providers, low use of public health facilities and increased outflows of patients from Bangladesh to hospitals abroad. The key obstacles to access to health services are insufficient infrastructure and poor quality of existing facilities, lack of medical equipment, scarcity of doctors due to high patient load, long distance to the facilities and long waiting times until facilities have been reached, very short appointment hours, lack of empathy of health professionals, their generally callous and casual attitude, aggressive pursuit of monetary gains, poor levels of competence and, occasionally, disregard for the suffering that patients endure without being able to voice their concerns-all of these service failures are reported frequently in the print media. Such failures can play a powerful role in shaping patients’ negative attitudes and dissatisfaction with healthcare service providers and healthcare itself.